Antibody protects against lethal infection with the neurally spreading reovirus type 3 (Dearing). - Virgin, H W (1988)
The mammalian reoviruses have provided a valuable model for studying the pathogenesis of viral infections of the central nervous system (CNS). We have used this model to study the effect of antibody on disease produced by the neurally spreading reovirus type 3 (Dearing) (T3). Polyclonal and monoclonal antibodies protect mice from fatal infection with T3 after either footpad or intracerebral virus challenge. Protection occurs with monoclonal antibodies directed against the viral cell attachment protein sigma 1, and with polyclonal antisera without T3 sigma 1 binding activity. In vivo protection occurs with both neutralizing and nonneutralizing monoclonal antibodies. Antibody-mediated protection does not require serum complement and, under specific circumstances, can occur via Fc-independent mechanisms. Antibody can protect mice when transferred up to 5 days after intracerebral challenge and up to 7 days after footpad challenge, times when high titers of virus are present in the CNS. Thus, antibody mediated protection against this neurally spreading virus does not require neutralizing antibody or serum complement and occurs even in the face of established CNS infection.